International Workshop on Dynamic Behaviour of Structures and Materials, Interaction and Friction Across the Strain Rates - PETER 2015 (Engineering Transactions, 2015)
The workshop will cover both theoretical modelling of the mechanical behavior of materials and structures under dynamic loading and all aspects related to friction and contact.